Effect of Oxytocin Treatment on Artificial Insemination with Frozen-Thawed Semen in Murciano-Granadina Goats - Viudes-De-Castro, María P.; Salvador, I.; Marco-Jiménez, Francisco; Gómez, Ernesto A.; Silvestre, Miguel A. (2017)
The site where the semen is deposited appears to be one of the most important factors affecting pregnancy of inseminated goats. In Murciano-Granadina (MG) goats, post-cervical insemination is achieved in a limited number of females. An effective way to increase fertility rate could be by increasing post-cervical inseminations. Effect of exogenous oxytocin application to facilitate the cervical penetration and its effect on kidding rate and prolificacy in MG goats were investigated. Oestrus was synchronized using progesterone-impregnated sponges for 11 days. Females were randomly divided into three groups (n = 190) and received either an i.v. injection of 100 or 200 IU of oxytocin or saline solution 15 min before being inseminated. Data on semen deposition depth were recorded for each animal using a catheter scaled in centimetres (up to 4 cm). Depth of semen deposition was affected by the oxytocin treatment (p < 0.05). Oxytocin enhanced cervical passage only with the dose of 200 IU compared with the control group, increasing the deposition depth (2.9 cm vs 1.9 cm). No significant effect of oxytocin treatment on kidding rate and prolificacy was detected. Depth of semen deposition affected kidding rate (p < 0.01). In conclusion, oxytocin treatment improved the depth of semen deposition in AI of MG goats, but kidding rate and prolificacy was not affected. More studies must be conducted to assess the minimal effective dose required for sufficient cervical dilation, and to determine the effects of such doses of oxytocin on uterine motility, sperm transport and fertility in goats.